Hollow Cylinder with Thermoelastic Modelling by Reduced Differential Transform - Sangita Baburao Pimpare; Chandrashekhar S. Sutar (IndoMS, 2022)
The term thermal stresses are related to mechanics of materials. The thermal stress is formed due to any changes in temperature of a material. The large change in temperature concludes to higher the thermal stresses. Also, there is an effect of thermal expansion coefficient on thermal stresses. The thermal expansion coefficient is different for different materials. In the present paper, the design of a mathematical model concerning the thermal stresses in hollow cylinder subject to the heat conduction with initial and boundary conditions have developed. The basic aim of this work is related to calculations of thermal stresses and thermoelastic displacement in the hollow cylinder by using the reduced differential transform method. The analytical solution is satisfied with the aim of special cases for the copper material properties. The numerical results are illustrated graphically by using mathematical software SCILAB.